2010
DOI: 10.1007/s00382-010-0937-5
|View full text |Cite
|
Sign up to set email alerts
|

A transitioning Arctic surface energy budget: the impacts of solar zenith angle, surface albedo and cloud radiative forcing

Abstract: Snow surface and sea-ice energy budgets were measured near 87.5°N during the Arctic Summer Cloud Ocean Study (ASCOS), from August to early September 2008. Surface temperature indicated four distinct temperature regimes, characterized by varying cloud, thermodynamic and solar properties. An initial warm, melt-season regime was interrupted by a 3-day cold regime where temperatures dropped from near zero to -7°C. Subsequently mean energy budget residuals remained small and near zero for 1 week until once again te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
272
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(301 citation statements)
references
References 53 publications
21
272
2
Order By: Relevance
“…1 bear some resemblance to real Arctic mixed-phase clouds. Supercooled liquid overlies ice, ice and snow fall gradually, updrafts and entrainment through a moist inversion supply new cloud water, and multiple cloud layers form in areas of both stable and moist adiabatic stratification (e.g., Morrison et al 2012;Sedlar et al 2011;Verlinde et al 2013). The most serious deficiencies of the simulations with the Lin-Purdue scheme are that new clouds are too commonly mixtures of ice and liquid because of the implementation of supersaturation adjustment (see the appendix) and that the scheme does not maintain enough supercooled liquid at low temperatures.…”
Section: A Time Evolution Of Temperature and Cloudsmentioning
confidence: 99%
“…1 bear some resemblance to real Arctic mixed-phase clouds. Supercooled liquid overlies ice, ice and snow fall gradually, updrafts and entrainment through a moist inversion supply new cloud water, and multiple cloud layers form in areas of both stable and moist adiabatic stratification (e.g., Morrison et al 2012;Sedlar et al 2011;Verlinde et al 2013). The most serious deficiencies of the simulations with the Lin-Purdue scheme are that new clouds are too commonly mixtures of ice and liquid because of the implementation of supersaturation adjustment (see the appendix) and that the scheme does not maintain enough supercooled liquid at low temperatures.…”
Section: A Time Evolution Of Temperature and Cloudsmentioning
confidence: 99%
“…Unlike the rest of the globe, MPS clouds tend to be the most common in the lower Arctic troposphere, except during winter and early spring when ice-only clouds are somewhat more frequent. The MPS clouds have a profound impact on the surface energy balance, since liquid water generates significantly more long-wave radiation to the surface than do ice clouds Sedlar et al, 2011;Wesslen et al, 2014), and hence on the surface melt and freeze (Fig. 4).…”
Section: Cloud Physicsmentioning
confidence: 99%
“…Despite this instability, liquid-topped clouds with ice and/or drizzle precipitating from this layer are the norm within the lower Arctic troposphere from spring through autumn (Tjernström et al, 2004;de Boer et al, 2009;Shupe, 2011;Sedlar et al, 2011). Shupe et al (2011) observed mean duration times of the order of 10 h for these cloud systems, but they may also occur as quasi-stationary systems persisting for days Sedlar et al, 2011;Shupe, 2011).…”
Section: Cloud Physicsmentioning
confidence: 99%
See 2 more Smart Citations